2014
DOI: 10.1002/hyp.10247
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency modulation and trend of the relationship between ENSO and precipitation along the northern to centre Peruvian Pacific coast

Abstract: Abstract:The relationship between El Niño Southern Oscillation (ENSO) and precipitation along the Peruvian Pacific coast is investigated over 1964-2011 on the basis of a variety of indices accounting for the different types of El Niño events and atmospheric and oceanographic manifestations of the interannual variability in the tropical Pacific. We show the existence of fluctuations in the ENSO/precipitation relationship at decadal timescales that are associated with the ENSO property changes over the recent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 45 publications
3
54
1
Order By: Relevance
“…Our results for regions B and D corroborate to some extent with the results in Bourrel et al . () and Vuille et al . ().…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Our results for regions B and D corroborate to some extent with the results in Bourrel et al . () and Vuille et al . ().…”
Section: Resultscontrasting
confidence: 66%
“…Bourrel et al . () showed that with exception of the strong 1982/1983 and 1997/1998 ENSO events, the region experienced increased (decreased) rainfall during EN years of the period 1964–1999 (2000–2011).…”
Section: Introductionmentioning
confidence: 97%
“…A careful quality check of these data was previously performed. Monthly precipitation, temperature, and streamflow data were homogenized and validated according to Bourrel et al (); Rau et al (); Rau et al (). Precipitation and temperature data were interpolated to a 5 × 5 km grid using inverse distance weighting interpolation and considering altitudinal gradients.…”
Section: Study Area and Datamentioning
confidence: 99%
“…. A careful quality check of this data was performed using the regional vector method similarly to what was performed in [3,4]. This dataset was interpolated at a spatial resolution of 1 km using a co-kriging method as in [4].…”
Section: Surface Water Record From the Dartmouth Flood Observatorymentioning
confidence: 99%
“…El Niño Southern Oscillation (ENSO) has a strong influence on rainfall patterns on the Pacific Coast of South America, from Ecuador to Chile, at an interannual time scale e.g., [1][2][3][4], affecting the likelihood of droughts and floods [5]. Positive anomalies of sea surface temperatures along the coast of Peru and Ecuador occurring during ENSO events induced torrential rains that cause high discharge and large flood events [6].…”
Section: Introductionmentioning
confidence: 99%